1967
DOI: 10.1037/h0025153
|View full text |Cite
|
Sign up to set email alerts
|

Procedural, situational, and interpersonal variables in individual intelligence testing.

Abstract: A number of conclusions emerge from the review of research in the field of individual intelligence testing, Departures from standard procedures are more likely to affect specialized groups than normal groups. Susceptibility to situational variables, especially discouragement, appears more frequently with younger than with older Ss. Rapport is an important variable in the E-S relationship. E differences occasionally appear, but reasons for the differences are not clear. E's experience is usually not a critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

1970
1970
1993
1993

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 74 publications
1
33
0
Order By: Relevance
“…Expectan cies can also affect interpretations (207). Examiner effects appear to be more likely on free-response tests but are not limited to them (164) , and can oc cur in indi vidual testing of intelligence (188 ).…”
Section: Smentioning
confidence: 98%
“…Expectan cies can also affect interpretations (207). Examiner effects appear to be more likely on free-response tests but are not limited to them (164) , and can oc cur in indi vidual testing of intelligence (188 ).…”
Section: Smentioning
confidence: 98%
“…In samples of cerebral palsied children, ranging in age from 3 to 14, correlations of .82 (Saslow, 1961) and .71 (Saslow & Larsen, 1963) (Sattler & Theye, 1967;Sattler & Tozier, 1971).…”
mentioning
confidence: 97%
“…The instructions to test administrators often emphasize the importance of adequate rapport between the administrator and the test-taker. Such an emphasis is explicit acknowledgement (supported by some empirical investigations, e.g., Gordon & Durea, 1948; see review by Sattler & Theye, 1967) that the motivation for performing well on an intelligence test is a critical ingredient for accurate measurement of maximal performance. However, as numerous investigators have demonstrated, both the physical state of the test-taker (e.g., time-of-day, arousal level; see Revelle, Humphreys, Simon, & Gilliland, 1980) and the psychological state of the test-taker (presence or absence of debilitating anxiety, incentives, motivation to succeed or fail, degree of interest in the testing situation) may significantly impact the level of test performance (Quereshi.…”
Section: IVmentioning
confidence: 99%